Keep flying / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2023)
Must I fly again? For I pity my tired wings Their colors are fading Their strength is decreasing Their flapping is like an old machine And the struggle of flying in the wind Or with the heat of the sun Or the cold of the snow just fallen Or the wet of the rain For I'm so scared of pain As my heart is still bleeding And tears are still falling My futile pieces of hopes are vanishing My fragile voices of comfort are diminishing Must I keep flying? Soaring into the sky? Roaring that I won't cry? No matter how the weather is changing? No matter how the future is hiding? As this journey never ends Success is not yet in my hands Until then, I must keep flying And silently keep praying...